The haunted bookshop - Morley, Christopher, 1890-1957 (Lippincott, 1955)
Roger Mifflin, whom we met in the author's 'Parnassus on wheels,' here keeps a secondhand bookshop in Brooklyn, N.Y. He takes in the young daughter of a friend to learn the book trade, and immediately a mystery develops.